Rainbow Vertex Antimagic Coloring 2-Connection paada Keluarga Graf Tangga - Ahmad Musyaffa' Hikamuddin; Dafik Dafik; Rafiantika Megahnia Prihandini (CGANT JOURNAL OF MATHEMATICS AND APPLICATIONS, 2022)
All graph in this paper are connected graph and simple graph. Let G = (V,E)be a connected graph. Rainbow vertex connection is the assignment of G that has interior vertices with different colors. The minimum number of colors from the rainbow vertex coloring in graph G is called rainbow vertex connection number. If wf(u) ̸= wf(v) for two different vertext u, v ∈ V (G) then f is called antimagic labeling for graph G. Rainbow vertex antimagic coloring is a combination between rainbow coloring and antimagic labeling. Graph G is called rainbow vertex antimagic coloring 2-connection if G has at least 2 rainbow paths from u − v. Rainbow vertex antimagic coloring 2-connection to denoted as rvac2(G). In this paper, we will study rainbow vertex antimagic coloring 2-connection on a family of graphs ladder that includes H-graph Hn for n ≥ 2, slide ladder graph SLn for n ≥ 2, and graph Octa-Chain OCn for n ≥ 2.